Structure–antitumor activity relationships of tripodal imidazolium-amino acid based salts. Effect of the nature of the amino acid, amide substitution and anion. Issue 48 (4th November 2021) - Valls, Adriana; Altava, Belén; Aseyev, Vladimir; Carreira-Barral, Israel; Conesa, Laura; Falomir, Eva; García-Verdugo, Eduardo; Luis, Santiago Vicente; Quesada, Roberto
Abstract : Imidazolium tripodal compounds derived from amino acids presented good cancer cell growth inhibition against different cancer cell lines, increasing the inhibition when in vitro experiments were carried out at acidic pHe . Abstract : The antitumor activity of imidazolium salts is highly dependent upon their lipophilicity that can be tuned by the introduction of different hydrophobic substituents on the nitrogen atoms of the imidazolium ring of the molecule. Taking this into consideration, we have synthesized and characterized a series of tripodal imidazolium salts derived from l -valine and l -phenylalanine containing different hydrophobic groups and tested them against four cancer cell lines at physiological and acidic pH. At acidic pH (6.2) the anticancer activity of some of the tripodal compounds changes dramatically, and this parameter is crucial to control their cytotoxicity and selectivity. Moreover, several of these compounds displayed selectivity against the control healthy cell line higher than four. The transmembrane anion transport studies revealed moderate transport abilities suggesting that the observed biological activity is likely not the result of just their transport activity. The observed trends in biological activity at acidic pH agree well with the results for the CF leakage assay. These results strongly suggest that this class of compounds can serve as potential chemotherapeutic agents.